An emergy analysis of environmental sustainability in urban agriculture: evidence from protected agriculture in Beijing, China - Yuan, Qiuling; Mi, Shiyu; Meng, Fanxin; Hou, Jiaqi; Sun, Yutong; Li, Hui; Shah, Aamir Mehmood (Frontiers in Sustainable Food Systems, 2023)
Urban agriculture (UA) serves as an essential aspect of local food production that could promote the urban resilience enhancement of food system. This study applies a "farm-to-table" emergy method to analyze the environmental sustainability of two typical urban farms in Beijing, China, based on the field investigation. One is a suburban greenhouse farm that sells food through supermarkets, and the other is an aquaponic farm that delivers fresh food to consumers' tables by express delivery. The results showed that compared with traditional greenhouse farming, aquaponics farm has a lower environmental loading ratio and higher emergy sustainability index, but requires more emergy inputs. The research findings would provide scientific references for the future planning of urban agriculture from the perspective of both production and sales.